1981
DOI: 10.1210/jcem-53-1-113
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ratio of Triiodothyronine to Thyroxine, and Thyroxine-Binding Globulin and Calcitonin Concentrations in Graves' Disease and Destruction- Induced Thyrotoxicosis*

Abstract: The serum ratios of T3 to T4, and T4-binding globulin (TBG) and calcitonin concentrations were studied in cases of thyrotoxic Graves' disease and destruction-induced thyrotoxicosis. In 272 patients with Graves' disease, 209 of 240 (87%) untreated patients without complications had high T3 to T4 ratios (nanograms per micrograms) of more than 20. Six of 32 (19%) patients with Graves' disease who had complications (15 with pregnancy, 14 with increased TBG, and 3 with conditions associated with a low T3 syndrome) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
2

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 26 publications
8
51
0
2
Order By: Relevance
“…On the other hand, we found no association between iodine intake from vitamin supplements and the degree of biochemical thyrotoxicosis at disease onset. Finally, TRAb-negative GD patients had mild thyrotoxicosis, which is in accordance with most (34,35,36) but not all studies (5). Based on our findings, two extremes of GD patients were identified: a group of women aged !40 years living in Copenhagen with only mild iodine deficiency and having measurable TRAb (high T 3 group), and at the other end of the spectrum a group of TRAb-negative patients aged R40 years who lived in and around Aalborg with moderate iodine-deficiency (low T 3 group).…”
Section: Determinants For Hormonal Levels In Gd Mntg and Stasupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, we found no association between iodine intake from vitamin supplements and the degree of biochemical thyrotoxicosis at disease onset. Finally, TRAb-negative GD patients had mild thyrotoxicosis, which is in accordance with most (34,35,36) but not all studies (5). Based on our findings, two extremes of GD patients were identified: a group of women aged !40 years living in Copenhagen with only mild iodine deficiency and having measurable TRAb (high T 3 group), and at the other end of the spectrum a group of TRAb-negative patients aged R40 years who lived in and around Aalborg with moderate iodine-deficiency (low T 3 group).…”
Section: Determinants For Hormonal Levels In Gd Mntg and Stasupporting
confidence: 87%
“…In addition, we found that GD patients had higher T 3 and T 4 levels compared with MNTG but not among those aged 80C years. It must be emphasized that there is a considerable overlap in serum T 3 and T 4 in the different subtypes both in this and in other studies (5,25,29). However, a serum T 3 R5.0 mmol/l (approximately twice the upper reference limit) was nearly only seen in patients with GD, where 52.6% had such severe abnormality compared with only 4.0/5.2% of patients newly diagnosed with MNTG/STA.…”
Section: Serum T 3 and T 4 In Subtypes Of Thyrotoxicosissupporting
confidence: 52%
See 1 more Smart Citation
“…Human chorionic gonadotrophin (HCG) produced by the placenta has a weak thyroid stimulatory effect and the rapid rise in HCG in early pregnancy is often accompanied by some alterations in serum thyroid hormone and thyrotropin (TSH) levels (Braunstein & Herhman, 1976;Yoshkawa et al, 1989;Pekonen et al, 1988). Also, the marked increase in the synthesis of thyroxine-binding globulin resulting from the increasing oestrogen levels affects the thyroid hormone homeostasis by expanding the thyroid hormone binding compartment (Glinoer et al, 1990;Ericsson & Threll, 1986;Amino et al, 1981). Further the extra need of iodine imposed by pregnancy can serve to unmask a mild iodine de®ciency as re¯ected in a relative hypothyroxinaemia and increasing maternal TSH levels (Glinoer et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Superior thyroid artery mean peak systolic velocity for the diagnosis of thyrotoxicosis in Japanese patients Toyoyoshi Uchida 1) , Kageumi Takeno 1) , Masahiro Goto 1) , Rei Kanno 1) , Sayaka Kubo 1) , Satomi Takahashi 1) , Kousuke Azuma 1) , Ken Sakai 1) , Yoshio Fujitani 1), 2) , Takahisa Hirose 1), 2) , Ryuzo Kawamori 1), 2), 3) and Hirotaka Watada 1) ultrasonography (EUB-525, Hitachi, Tokyo) with a 10-MHz linear transducer. Thyroid volume was calculated using the ellipsoid model ((width x length x thickness x π/3) for each lobe + (width x length x thickness) for isthmus).…”
mentioning
confidence: 99%